The Origin and Evolution of the Korean Economic System - Wonhyuk Lim (Korea Development Institute (KDI), 2000)
Unlike the typically ahistorical arguments that try to explain the 1997 economic crisis by simply dismissing even the very existence of Koreas economic success in the past, this paper has attempted to provide an alternative explanation using the concept of path dependence within a political economy context. Applying the QWERTY paradigm to the evolution of the Korean economic system, the paper has argued that the very success of the system created a coalition of economic players interested in preserving the system, even when it became increasingly dysfunctional in a changed environment. The paper has covered four main topics: (1) the adoption of the Korean economic system, (2) the initial success of the system, (3) the seeds of failure in the system, and (4) the persistence of the system. The main arguments of the paper are summarized in the remaining pages.
Keywords: 330